The role of polymorpisms in glutathionerelated genes in asbestos-related diseases - Franko, Alenka (Radiology and oncology (Ljubljana), 2021)
The study investigated the influence of GCLC, GCLM, GSTM1, GSTT1 and GSTP1 polymorphisms, as well as the influence of interactions between polymorphism and interactions between polymorphisms and asbestos exposure, on the risk of developing pleural plaques, asbestosis and malignant mesothelioma (MM). Subjects and methods. The cross sectional study included 940 asbestos-exposed subjects, among them 390 subjects with pleural plaques, 147 subjects with asbestosis, 225 subjects with MM and 178 subjects with no asbestos-related disease. GCLC rs17883901, GCLM rs41303970, GSTM1 null, GSTT1 null, GSTP1 rs1695 and GSTP1 rs1138272 genotypes were determined using PCR based methods. In statistical analysis, logistic regression was used. Results. GSTT1 null genotype was associated with the decreased risk for pleural plaques (OR = 0.63; 95% CI = 0.40% 0.98; p = 0.026) and asbestosis (OR = 0.51; 95% CI = 0.28%0.93; p = 0.028), but not for MM. A positive association was found between GSTP1 rs1695 AG + GG vs. AA genotypes for MM when compared to pleural plaques (OR = 1.39; 95% CI = 1.00%1.94; p = 0.049). The interactions between different polymorphisms showed no significant influence on the risk of investigated asbestos-related diseases. The interaction between GSTT1 null polymorphism and asbestos exposure decreased the MM risk (OR = 0.17; 95% CI = 0.03%0.85; p = 0.031). Conclusions. Our findings suggest that GSTT1 null genotype may be associated with a decreased risk for pleural plaques and asbestosis, may modify the association between asbestos exposure and MM and may consequently act protectively on MM risk. This study also revealed a protective effect of the interaction between GSTP1 rs1695 polymorphism and asbestos exposure on MM risk.
Keywords: asbestos; azbestoza; geni; glutathione-related genes; malignant mesothelioma; maligni mezoteliom; polimorfizmi; polymorphisms